Controversies in contrast-enhanced ultrasound (CEUS): pregnancy, paediatric, abdominal trauma, complex renal cysts, and endovascular aortic repair follow-up - Paul S. Sidhu; Dirk Andre Clevert; Annamaria Deganello; Maciej Piskunowicz; Vito Cantisani; Thomas Fischer; European Society of Radiology (ESR) (Insights into Imaging)
Abstract The use of contrast-enhanced ultrasound (CEUS) in clinical practice is theoretically limited to the licensed indications: focal liver lesions, breast, peripheral arterial system, and the heart. In reality, there has been a continuous expansion of the deployment of CEUS examinations to many other organs and body parts over the last 20 years. Many of these applications are a natural extension of the diagnostic capabilities of the CEUS examination, used to achieve a better imaging outcome. These applications have been supported by guidelines issued by scientific societies, detailing the application, accuracy, and safety of the clinical performance. Nevertheless, there are some areas in which it remains more difficult to establish the use of CEUS in the diagnostic pathway. In the pregnant patient, CEUS is an ideal examination—a natural extension of B-mode ultrasound, avoiding ionising radiation and iodinated contrast. The contrast agents used in ultrasound do not cross the placental barrier. Ultrasound in the paediatric patient is used widely, and extending this to a CEUS examination improves diagnostic capabilities, avoiding less child-friendly imaging techniques. The parent can be in the room at the time of the ultrasound examination. Other aspects of CEUS usage are hampered by the lack of physician engagement despite the proven advantages of the technique, the reduction in the morbidity associated with CT and MR imaging, particularly the contrast agents used in these modalities. Complex renal cyst classification, follow-up of blunt abdominal trauma and the surveillance following placement of an aortic stent graft are all areas of potential benefit to the diagnosis. All these are better imaged on a CEUS examination. Furthermore, cost savings can be achieved using CEUS, mostly by alleviating downstream costs of CT and MR imaging. Critical relevance statement CEUS use outside licensed uses is becoming established, driven by the unique ability to achieve diagnostic standards safely and with patient acceptability, pushing the boundaries in areas of abdominal trauma, pregnancy, paediatrics, aortic implants, and complex renal cysts. Key Points CEUS has a narrow range of licensed applications in medical imaging, but is used widely. An exclusively intravascular agent allows assessment of vascular flow at the capillary level. CEUS is extremely safe and can be used in many areas that require repeated high-resolution imaging.